PENGARUH INOVASI ORGANISASI TERHADAP PENCAPAIAN INDIKATOR KINERJA UTAMA: (Studi pada Dinas Perikanan Kabupaten Banyuwangi) - Sekti, Adam Raka; Sjamsuddin, Sjamsiar; Hayat, Ainul (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2025)
The Influence of Organizational Innovation on the Achievement of Key Performance Indicators (Study at the Banyuwangi Regency Fisheries Service). The fisheries sector is a key focus of the government to boost non-oil exports, create jobs, generate foreign exchange, and improve nutrition. However, many coastal communities involved in fisheries still face poverty that needs targeted solutions. One effective effort is implementing measurable organizational innovation. This study analyzed the impact of such innovations on key performance indicators (IKU) at the Banyuwangi Regency Fisheries Service. Using a quantitative associative method, data were gathered through surveys, interviews, and observations involving employees, fishermen, and fish farmers. The results showed that innovations like streamlining procedures, adopting digital technology, and strengthening community collaboration significantly improved fisheries production and fish consumption as performance indicators. These findings confirm that organizational innovation effectively enhances public service quality in the fisheries sector.